Organization science as social construction: postmodern potentials - Gergen, Kenneth J.; Thatchenkery, Tojo Joseph (2004)
We critically examine three major assumptions of modernist organization science: rational agency, empirical knowledge, and language as representation. With these assumptions problematized, we are positioned for postmodern turn in the discipline. From a postmodern standpoint, we are moved to replace rational agency with communal rationality, empirical knowledge with social construction, and language as representation with language as action. Outcomes for an organization science place special emphasis on reconstructing and enriching the aims and methods of research and on critical reflection, generative theorizing, and scholarly action within organizations. -Reproduced.
Keywords: Organizations